Inﬂuence of RF-sputtering power on formation of vertically stacked Si1−xGex nanocrystals between ultra-thin amorphous Al2O3 layers: structural and photoluminescence properties - Vieira, E. M. F. (2013)
The authors would like to thank Professor David J Barber (University of Essex) for his helpful discussions and critical reading of this manuscript, and Engineer José Santos for technical support at Thin Film Laboratory.